FROM EXCLAMATION TO POETIC SHAPING: THE FUNCTIONS AND AESTHETIC TRANSFORMATION OF INTERJECTIONS IN CHINESE POETRY - Sun Jiaze; Mulyadi (Lire Journal (Journal of Linguistics and Literature), 2026)
Interjections and exclamatory particles have often been treated as marginal linguistic forms because they appear syntactically detached, semantically unstable, and strongly dependent on context. In poetry, however, these small units may become concentrated sites of rhythm, emotional pressure, tonal transition, and aesthetic organization. This article examines the functions of interjections in Chinese poetry from early and classical traditions to modern poetry. Using a qualitative, text-based design, the study combines close reading, comparative textual analysis, and historical-poetic interpretation. The corpus consists of selected passages from the Canglang song and Chuci tradition, Li Bai’s Shu Dao Nan, Su Shi’s Qian Chibi Fu, Wen Yiduo’s Hongzhu, and selected poems by Mu Dan. The analysis is organized through five operational indicators of what this article calls the poetic shaping function: rhythmic shaping, tonal shaping, structural shaping, subjective or embodied shaping, and cultural shaping. The findings show that in classical poetry forms such as xi, hu, zai, and related exclamatory particles, condense emotion while also regulating cadence and rhetorical pressure. In later classical usage, these particles accumulate cultural memory and transform direct exclamation into lament, reflection, and philosophical modulation. In modern poetry, especially in Wen Yiduo and Mu Dan, interjections become more visible and structurally active: a and o/oh not only express emotion but also organize address, pause, perception, bodily tension, and modern subjectivity. The study argues that interjections are therefore not peripheral residues of speech but formative aesthetic micro-units in Chinese poetic language.